African experiment : cooperative agriculture and banking in British West Africa - DeGraft-Johnson, John Coleman (London : Watts, 1958)
This book attempts to dispel ignorance about the economic development of British West Africa and to remove some of the misconceptions which arise from inaccurate teaching about the 'Dark Continent'
Includes bibliography.
gp. 23/01/2019
loan
Keywords: Agriculture, Cooperative; Agricultural cooperative credit associations